EFL GRADUATE STUDENTS’ VOICES ON THEIR TECHNOLOGY-INTEGRATED CLASSROOM LANGUAGE TASKS - Mali, Yustinus Calvin Gai (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
This qualitative study delves closely into graduate students’ reflective-evaluative voices on technology-integrated classroom language tasks they found useful and challenging in Introduction to Digital Technology (IDT) class in an English as a Foreign Language (EFL) setting at a private university in Central Java, Indonesia. The study also focuses on exploring the students’ practical recommendations to improve the quality of teaching and learning activities in the class. To meet the research goals, seven EFL graduate students participated in this study by answering closed and open-ended questions in a Google Form. For data triangulation, three of them participated in an in-depth semi-structured interview to clarify their responses to the questionnaire. The research findings inform that writing the literature review discussing realities of technology use in schools and districts in Indonesia and writing the report for technology workshop activities for school teachers seemed to be the most useful activities for the students in the IDT class. Besides the writing parts, conducting the technology workshop for the school teachers was another useful activity for the students. Although useful, the students considered the writing activities as one of the most challenging tasks in the course. Other findings, including reasons why the students found the tasks useful and challenging, as well as practical ways to improve the teaching and learning activities in the class, were then discussed in light of the relevant literature. The overall discussions might tell the success and challenges of the integration of technology in language teaching and learning, research, and community service activities in a higher education context in Indonesia. Recommendations for future research are presented.